Desain Pembelajaran IPS Berbasis Teknologi Informasi di Sekolah Dasar - Syarifuddin, Syarifuddin; Anjarwati, RR Ani; Aisyah, St; Putro, Herry Porda Nugroho; Triana, Yuli (Jurnal PGSD, 2022)
This article aims to provide information and describe the design of IT-based social studies learning. Learning design is urgent to improve the development, creation and design of learning activities. In this era of the Industrial revolution, IT-based learning is very urgent to support the learning process. Teachers must be able to apply it to learn. This research uses a literature study method, data is collected by conducting searches and exploring journals through search engines and books and other supporting data. The results of several journals found indicate that the influence of IT is very large in the world of education so it is used as an IT-based learning medium. The media developed learning content including social studies learning.